Finite element analysis of the dynamic response of planar coupled shear walls - Gutierrez, Marte S.
The finite element method was used to analyze the dynamic characteristics and seismic responses of planar coupled shear walls. The conventional 8-d.o.f. plane stress rectangular finite element with linear edge displacement and a lumped mass formulation was used. Two coupled shear wall problems were solved. The first is for the analysis of root convergence of the finite element formulation while the second is an application to a coupled shear wall building. A computer program was developed to solve the eigenvalue problem using the subspace iteration technique. Seismic response analysis was made using the response spectrum technique and the 1940 El Centro earthquake as input. Results were compared with the continuum method and Uniform Building Code provisions. The comparisons show significant differences in the results.